1995
DOI: 10.1677/jme.0.0140157
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the cDNA encoding the human neuromedin U (NmU) precursor: NmU expression in the human gastrointestinal tract

Abstract: Many peptide precursors encode more than one bioactive peptide. Recent cloning of the rat neuromedin U (NmU) precursor revealed potential proteolytic processing sites which may generate three associated peptides in addition to the NmU peptide, which is known to have potent uterine contractile effects. To assess the degree of evolutionary conservation, which often suggests conserved biological function and hence physiological importance, we have cloned and sequenced the cDNA encoding the human NmU precursor. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 0 publications
3
57
0
1
Order By: Relevance
“…Considering these results together, the reported action of neuromedin U on uterine tissue would appear to be primarily mediated by TGR-1. It has been reported that both neuromedin U mRNA and neuromedin U-like immunoreactivity are abundantly detected in the human and rat pituitary gland (17,24,25). We detected the highest level of neuromedin U mRNA expression in the rat pituitary gland (10).…”
Section: Discussionsupporting
confidence: 46%
“…Considering these results together, the reported action of neuromedin U on uterine tissue would appear to be primarily mediated by TGR-1. It has been reported that both neuromedin U mRNA and neuromedin U-like immunoreactivity are abundantly detected in the human and rat pituitary gland (17,24,25). We detected the highest level of neuromedin U mRNA expression in the rat pituitary gland (10).…”
Section: Discussionsupporting
confidence: 46%
“…In human tissue, NmU mRNA is found in the intestine, stomach, pituitary gland and several brain regions, including hypothalamus, locus coeruleus, thalamus, medulla and substantia nigra; it is also found in lymphoid cells (Sumi et al 1987, Austin et al 1995, Raddatz et al 2000. A similar expression pattern is observed in rat (Domin et al 1987, Fujii et al 2000 and mouse (Funes et al 2002).…”
Section: Introductionmentioning
confidence: 59%
“…Two active peptides were identified in this work: an amidated 25-amino-acid peptide that is generated by enzymatic cleavage at the C-terminal region of a 174-amino-acid precursor (Lo et al 1992) and an 8-amino-acid cleavage product of NmU-25 (NmU-8) (Minamino et al 1985b), both of which possess smooth muscle contractile activity (Minamino et al 1985a,b). NmU cDNAs from dog, rabbit, frog, rat and human have been cloned (Domin et al 1989, Kage et al 1991, O'Harte et al 1991, Lo et al 1992, Austin et al 1995 and demonstrate a strong amino-acid sequence homology. In particular, it has been shown that the C-terminal heptapeptide core of NmU (FLFRPRN-NH 2 ) constitutes a conserved domain that is sufficient for biologic activity (Hashimoto et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Neuromedin U (NMU) is a highly conserved brain-gut peptide that was first isolated from the porcine spinal cord (Minamino et al 1985) and later from the brain, spinal cord, and intestine of other species (Domin et al 1986, 1989, O'Harte et al 1991, Austin et al 1995. Thus far, the only known physiological role of NMU is contraction of smooth muscles in blood vessels, the uterus, and the gastrointestinal tract (Minamino et al 1985).…”
Section: Introductionmentioning
confidence: 99%